Fluency with information technology : Skills, concepts and capabilities - Snyder, Lawrence (Boston Pearson, 2011)
This book equips readers who are already familiar with computers, the Internet, and the World Wide Web with a deeper understanding of the broad capabilities of technology. Through a project-oriented learning approach that uses examples and realistic problem-solving scenarios.
Keywords: Công nghệ thông tin